Identification of Accident Hot Spots: A GIS Based Implementation for Kannur District, Kerala - Deepthi Jayan.K and B.Ganeshkumar (INTERNATIONAL JOURNAL OF GEOMATICS AND GEOSCIENCES, 2010)
Accident analysis studies aim at the identification of high rate accident locations and safety deficient areas. In this study, an effort ahs been made to identify the accident prone zones within Kannur district, Kerala using GIS. For this purpose, the road accident data for the years 2006, 2007 and 2008 pertaining to Kannur district have been used. Accident particulars like date, location, type of vehicle involved, number of persons injured or died are included in the GIS database. Accident analysis studies aim at the identification of high rate accident locations and safety deficient areas. The “Density” function available in the spatial analyst extension of the Arc GIS software was applied to identify the accident prone areas in Kannur district during the years 2006, 2007 and 2008. Both simple and Kernal densities were applied in identifying the accident patterns. The road geometry was measured in the accident prone locations to find out the causes for the accident. Based on the result, suggestions are provided to reduce the accidents in the future